KAJIAN AWAL PENGARUH WAKTU REAKSI DAN RASIO MOLAR ASAM OLEAT DENGAN BUTANOL TERHADAP SIFAT FISIKO KIMIA PLASTISIZER BUTIL OLEAT - Selly, Mers; -, Nirwana (Jurnal Riset Kimia, 2014)
Vol 7 No 2ABSTRACTEsterification reaction is a reaction between fatty acids or carboxylic acids with alcohols toesters. Fatty acid (oleic acid) sourced from palm oil. One alternative to increase the economicvalue of palm oil is oleic acid esterification into oleic butyl known as plasticizers. Plasticizeradditives are compounds added to polymers to improve its flexibility and workabilitas. Thisstudy aims to study the effect of reaction time and molar ratio of the plasticizer synthesis oleicbutyl and identify the plasticizer oleic butyl. In this study, the first step is preparation H-Zeolitecatalyst, then synthesis of plasticizer butyl oleic esterification using natural zeolite catalystswere activated to H-zeolites with variables in the reaction time (6, 9 and 12 hours) and themolar ratio of oleic acid and butanol (1: 6, 1: 9 and 1:12) with the permanent variable stirringspeed of 200 rpm, 108-112 Â° C of temperature and the catalyst were 15% oleic acid-based. Fromthe test results obtained 0.862 specific gravity, viscosity of 8.39 mPa and showed that thespecific gravity and viscosity of the resulting plasticizer has commercial plasticizer standardnamely 0.862 to 0.928 and from 8.2 to 9.4. Optimal operating conditions obtained in thisresearch is the molar ratio of 1:12, reaction time 12 hours resulted in a conversion reaction of76.73%.Keywords: Esterifikasi, H-zeolite, Oil, Plasticizer